2020
DOI: 10.1080/10717544.2020.1736208
|View full text |Cite
|
Sign up to set email alerts
|

Fibroin nanoparticles: a promising drug delivery system

Abstract: Fibroin is a dominant silk protein that possesses ideal properties as a biomaterial for drug delivery. Recently, the development of fibroin nanoparticles (FNPs) for various biomedical applications has been extensively studied. Due to their versatility and chemical modifiability, FNPs can encapsulate different types of therapeutic compounds, including small and big molecules, proteins, enzymes, vaccines, and genetic materials. Moreover, FNPs are able to be administered both parenterally and non-parenterally. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
96
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(97 citation statements)
references
References 140 publications
0
96
0
1
Order By: Relevance
“…Considering that sodium alginate could form an insoluble hydrogel at acidic condition, we employed it as the vehicle for oral administration of NR/RESms (Pham & Tiyaboonchai, 2020 ). Before in vivo administration, drug release behavior was investigated in vitro.…”
Section: Resultsmentioning
confidence: 99%
“…Considering that sodium alginate could form an insoluble hydrogel at acidic condition, we employed it as the vehicle for oral administration of NR/RESms (Pham & Tiyaboonchai, 2020 ). Before in vivo administration, drug release behavior was investigated in vitro.…”
Section: Resultsmentioning
confidence: 99%
“…Fibroin has many advantages as a drug delivery system; however, it still has disadvantages to overcome. Since sericin can cause an immune function, the process of removing sericin from silk fibers must be properly completed [ 35 ]. In addition, the slow degradation of the fibroin crystalline antiparallel β-sheet domain can be a disadvantage in terms of some applications that require fast and complete removal of nanoparticle carriers ( Table 1 ).…”
Section: Types Of Proteins Used To Produce Protein Nanoparticlesmentioning
confidence: 99%
“…Fibroin, as the main silk protein, has an array of properties that enable it to be an efficient biomaterial for drug delivery. For these reasons, several studies have shown promising results with the encapsulation of curcumin in silk fibroin NPs [ 98 , 99 ]. Curcumin-loaded silk fibroin NPs have proved higher efficacy in cytotoxicity against neuroblastoma cells than hepatocarcinoma cells [ 100 ], also displayed by the in vitro enhancement of antioxidant and anti-inflammatory properties and increase in healthy cell viability.…”
Section: Curcumin-loaded Colloidal Delivery Systemsmentioning
confidence: 99%